2013
DOI: 10.1002/bmc.3005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and tissue distribution of paclitaxel in rabbits assayed by LC‐UV after intravenous administration of its novel liposomal formulation

Abstract: A simple, rapid and sensitive LC-UV method was developed and validated for the determination of paclitaxel (PTX) in rabbit plasma and tissues. A 2 mL aliquot of acetonitrile and 10 μL ammonium acetate (pH 5.0, 6 m) as extraction agents were used to markedly increase the extraction recoveries and greatly reduce the endogenous substances. The separation was achieved on a C18 column at 30 °C using an acetonitrile-ammonium acetate buffer (pH 5.0, 0.02 m; 55:45, v/v) at a flow rate of 1.0 mL/min; UV detection was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…[22][23][24][25][26][27][28] Furthermore, the liposomes can improve the oral bioavailability of drugs poorly absorbed through the gastrointestinal tract and alter the in vivo distribution of the drugs encapsulated into liposomes, to increase the therapeutic index. 22,[29][30][31][32] Currently, liposomes have been considered one of the most promising drug delivery carriers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[22][23][24][25][26][27][28] Furthermore, the liposomes can improve the oral bioavailability of drugs poorly absorbed through the gastrointestinal tract and alter the in vivo distribution of the drugs encapsulated into liposomes, to increase the therapeutic index. 22,[29][30][31][32] Currently, liposomes have been considered one of the most promising drug delivery carriers.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, due to its low hydrophilicity and poor absorption following oral administration, the low oral bioavailability of BA limits its therapeutic efficacy and clinical application. 13,16 Therefore, on the basis of our previous studies, 23,24 the novel effervescent dispersion technique was used to develop BA-LP for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding can be attributed to the protection provided by the lipid membranes and slow drug release from the formulation. 59 A previous in vitro report by Paliwal et al indicated that pretreatment of cells with ultrasound may change the concentration of quercetin in treated cell lines. 27 Our in vivo experiment demonstrated that the C 5 min increased from 0.5±0.1 μg/mL to 0.9±0.2 μg/mL after treatment with ultrasound (Table 2).…”
mentioning
confidence: 99%